Histopathology turnaround time of surgical biopsies in a Nigerian tertiary health-care facility (2021)
Background: Turnaround time (TAT) analysis is finding increasing relevance in clinical laboratories due to its relevance in the quality of care of patients. TAT involves all the various processes that occur within the laboratory. Aims: The aim of this study was to analyze the histopathology TAT of surgical biopsies at the Department of Pathology, University College Hospital (UCH), Ibadan. Materials and Methods: This was a retrospective analysis of 1085 samples received at the Department of Pathology, UCH, Ibadan, from January to April 2020. Samples were categorized into small, intermediate, and large sizes. Average duration spent in the grossing room, processing, reporting, and result verification was calculated, and the total TAT was determined from the summation of the duration of these processes. Results: The mean TAT for all samples was 22 days(±10 days). Reception grossing, histological processing, reporting, and transcription accounted for an average of 1.5 (7%), 5.9 (27%), 9.1 (41%), and 5.6 (25%) days and percentage of TAT, respectively. There was no significant difference in the mean TATs for small , intermediate-, and large-sized samples. Conclusion: We identified reporting time as the largest contributor to TAT. Other areas of delay were noted at tissue processing and result verification. Adoption of new technology and staff orientation may help to reduce the observed TAT.